Diversity, Conservation Status and Traditional uses of Family Zingiberaceae in Nong Phok District, Roi Et Province - เพชรภักดี ฐนันดร์ศักดิ์; แสนสุข สุรพล; แสนสุข ปิยะพร (Koch Cha Sarn Journal of Science, 2021)
Study on diversity, conservation status and traditional uses of Zingiberaceae in Nong Phok District, Roi Et Province was conducted during August to February 2019. Eighteen species, eight genera and three tribes were collected. The most diversity has been found in genus Curcuma, Globba, Kaempferia and Zingiber (each three species). While, Alpinia and Boesenbergia (each two species) are reported for the second most diversity. The last diversity has been found in genus Amomum and Etlingera (each 1 species). Moreover, Boesenbergia xiphostachya (Gagnep.) Loes., Globba laeta K. Larsen, G. panicoides Miq., G. winitii C.H. Wright are recognized as rare species. G. laeta is reported as endemic plant. K. siamensis is reported as vulnerable species. The traditional uses have been found in four categories which were foods, medicines, ornamental plants and faith.